2014
DOI: 10.1002/jbm.b.33237
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable ureteral stents from natural origin polymers

Abstract: In this work, stents were produced from natural origin polysaccharides. Alginate, gellan gum, and a blend of these with gelatin were used to produce hollow tube (stents) following a combination of templated gelation and critical point carbon dioxide drying. Morphological analysis of the surface of the stents was carried out by scanning electron microscopy. Indwelling time, encrustation, and stability of the stents in artificial urine solution was carried out up to 60 days of immersion. In vitro studies carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Equilibrium water uptake was found to be around 3000 wt % for all tested formulations. Another study with alginate hydrogel demonstrated similar values [47]. The samples were found to be stable in PBS solution and degraded after 21 days.…”
Section: Water Uptake and Weight Losssupporting
confidence: 53%
“…Equilibrium water uptake was found to be around 3000 wt % for all tested formulations. Another study with alginate hydrogel demonstrated similar values [47]. The samples were found to be stable in PBS solution and degraded after 21 days.…”
Section: Water Uptake and Weight Losssupporting
confidence: 53%
“…This helps to understand that with higher amounts of gelatin in the formulation a faster degradation will take place. In our previous study, the alginate-based ureteral stents showed a slower degradation comparing with this work, for the same reason [16]. The polymer blend with the alginate is however unknown and hence difficult to establish a work correlation compared with our formulation.…”
Section: In Vitro Degradation Studymentioning
confidence: 49%
“…Other studies using poly(lactic-co-glycolic acid)-based ureteral stents reported favorable radiopaque and drainage properties, but the biocompatibility was compromised, according to what is reported in the literature [5,[13][14][15]. The degradation of the ureteral stents must be uniform and homogenous or dissolving based on directionality, preventing the formation of fragments during the degradation process that can block the ureter [1,6,16]. Uriprene stent (Poly-Med, USA), a radiopaque, glycolic-lactic acid based stent has been designed to degrade in the direction of the bladder coil to renal coil preventing ureteral obstruction secondary to degrading stent fragments [1].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations